Quality of Public Services with the Utilization of Digital Platforms in Perumdam - Salzabila Haryani; Herlina Nur W; Winda Winda; Muhamad Gani Akbar; Siti Khumayah; Khaerudin Imawan (Asian Journal of Social and Humanities, 2024)
The government is responsible for providing various aspects of state life, including services to meet health and education needs. The importance of this research is to determine how Perumdam Tirta Darma Ayu uses digital platforms to improve the capabilities of its human resources and solve unsolved problems. The headquarters of the Tirta Darma Ayu Regional Public Company for Drinking Water is the location of this qualitative research. This research collects data through interviews, documentation, and observation. Instead, this study uses the dimensions of strategy, human resource capacity, and service quality. Three suboptimal aspects: reliability, responsiveness, and empathy are the things that many customers complain about. experiencing problems with the complaint service information system that uses digital platforms. According to this study, public service human resources are still less able to use digital platforms. Therefore, the researcher suggests several methods, such as automating quality, building and developing a Service Information system, adding qualified technicians, providing instructions on how to communicate customer wishes, and providing clear and accurate information.